Opportunities and perspectives for green chemistry in semiconductor technologies. Issue 12 (31st May 2019) - Iacopi, Francesca; McIntosh, Monique
Abstract : Semiconductor technologies offer a plethora of technological challenges and opportunities for a more extensive implementation of green chemistry principles. Abstract : Semiconductor chip manufacturing has one of the highest environmental footprints within the electronics life cycle. This sector offers a plethora of technological challenges and opportunities for implementing green chemistry principles more extensively. In addition to technical solutions, a renewed collaborative focus on green chemistry throughout the ecosystem of the semiconductor industry, particularly in the pre-competitive stage, will be fundamental to seeing those solutions through to implementation.